Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1002/app.50588
|View full text |Cite
|
Sign up to set email alerts
|

High‐performance thermosets with tailored properties derived frommulti‐armstared vanillin and carbon fiber composites

Abstract: Vanillin, a rigid compound can be separated from lignin, is a promising sustainable candidate for industrial and high performance polymers, while synthesis of hexa-epoxies is challenging. Meanwhile, carbon fiber reinforced biobased polymers combining high performance are more difficult to be achieved because of the contradictions of liquidity and high rigidity in the polymer structure and performance. In this paper, a novel hexa-epoxy functionalized bio-based epoxy resin (HPVIGEP) with a multi-arm star structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Phenolic resins from biomasses have been indeed developed and studied extensively in recent decades, but the search for biobased alternative to standard phenolic in the specific sector of high charring matrices is still ongoing (Loganathan et al, 2021), even though it is predictable that the properties of resin synthesized from bioresources are lower than the raw material derived from oil (Ipakchi et al, 2020;Ma et al, 2020;Guo et al, 2021;Gruber et al, 2021). One example of nanofiller reinforced phenolic composites for ablative purposes comes from the paper of Ma et al, where the authors found that the addition of graphene oxide or graphitic carbon nitride (Figure 8C) (Ma et al, 2019) increased the char yield graphitization level during ablation, helping heat dissipation and thereby increasing the ablation resistance.…”
Section: Phenolicsmentioning
confidence: 99%
“…Phenolic resins from biomasses have been indeed developed and studied extensively in recent decades, but the search for biobased alternative to standard phenolic in the specific sector of high charring matrices is still ongoing (Loganathan et al, 2021), even though it is predictable that the properties of resin synthesized from bioresources are lower than the raw material derived from oil (Ipakchi et al, 2020;Ma et al, 2020;Guo et al, 2021;Gruber et al, 2021). One example of nanofiller reinforced phenolic composites for ablative purposes comes from the paper of Ma et al, where the authors found that the addition of graphene oxide or graphitic carbon nitride (Figure 8C) (Ma et al, 2019) increased the char yield graphitization level during ablation, helping heat dissipation and thereby increasing the ablation resistance.…”
Section: Phenolicsmentioning
confidence: 99%